If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c + 11 = -30 Reorder the terms: 11 + c = -30 Solving 11 + c = -30 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + c = -30 + -11 Combine like terms: 11 + -11 = 0 0 + c = -30 + -11 c = -30 + -11 Combine like terms: -30 + -11 = -41 c = -41 Simplifying c = -41
| 5x+11=3x+9 | | 12-10x+11x=6 | | n-m=14 | | 5x-2+x=3x-4-5 | | 5x-2-4x=1-11 | | 6.6=14.4 | | 29+8x=51-3x | | 2x-2=2x-32 | | X^2-y^2-x-y=0 | | 5z-2-4=1-11 | | 4x+21=12-67 | | 8x+6=9x-9 | | 5x-9=4x-13 | | z-5.2=17.8 | | 3x(x-1)-24=2x^2+x^2+3x | | -4x-7+10x=-7+6z | | 8+9x-7(5x-7)=8x | | 10y^6/2y^2 | | 8(s-10)=132 | | T+8=4t-7 | | x(.25)+y(.10)=6.05 | | -(x-1)/57 | | 6w+5y+8x+7x+-12y+4w= | | 3x-12=4-5x | | 1-7b=-3 | | xf(y)+yf(x)=(x+y)*f(x)*f(y) | | 2x+7=14x-41 | | |x|/4=5 | | f(x)=-.67x^2+8x+24 | | 16x+12=-1+17x | | xf(y)+yf(x)=(x+y)f(x)f(y) | | x-(x*0.1957)-64.84=400 |